Approximate Solution of Initial Value Problems by Means of Ninth Degree Spline - Hamasalh, Faraidun K. (Sulaimani Journal for Pure and Applied Sciences, 2014)
In this paper, a nonlinear initial value problem is solved numerically by means of ninth degree spline function. The solution of initial value problems approximated as a linear interpolation of ninth spline functions. In this method, the basis spline functions are redefined into a new approximation set of ninth degree spline functions which interpolate the number of select derivatives. To test the efficiency of the method, two numerical examples of initial value problems are solved by the proposed method.
Keywords: and phrases Spline function; convergence analysis; bounded errors; nonlinear IVPs